Studi Komparatif Asuransi Shari’ah dan Konvensional - Moh. Asra; Rizqiyah Rizqiyah (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2019)
Insurance is an institution engaged in services and helping people. In Arabic, insurance is called "Al-ta’m?n", means to provide protection. According to the National Sharia Board-Indonesian Ulama Council (DSN-MUI), shari'ah insurance is an effort to protect one another and to help one another among people or groups through investments in the form of assets or tabarru’ funds (endowment), and repayment. The essential of the Islamic insurance implementation is cooperation (ta'âwun). To maintain consistency in the implementation of sharia in the financial sector and the enhancement of the nation’s prosperity, tabarru’ funds (endowment) are considered to be the same as grants (donation) so that the funds donated cannot be canceled. There are fundamental differences between conventional insurance and shari’ah insurance because shari’ah insurance uses the principle of risk-sharing so that sharia insurance companies called the operators wouldn’t call the guarantors. Customers in sharia insurance companies called participants wouldn’t call guaranteed. Besides other differences are the contract, premium elements, ownership of fund, investment of fund, payment of claims, profit sharing, there is Sharia Supervisory Board, vision and mission, accounting methods, there is no charred fund, and there is no charge (loading).